Moringa oleifera as Anticancer: A Review of Recent Studies - Kambuno, Norma Tiku; Purwaningsih, Erni Hernawati (JURNAL INFO KESEHATAN, 2024)
Moringa oleifera Lam (MO) plants have long been reported to have many pharmacotherapy benefits. In vitro and in vivo studies have shown that MO extracts have various biological activities and therapeutic effects, including cardioprotective, cardiometabolic, hypocholesterolemic, neuroprotective, anti-inflammatory, antioxidant, anti-hypertensive, anti-diabetic, anti-bacterial, immunomodulatory and anticancer. Researchers have tested extracts from various parts of the MO tree, both in vitro and in vivo, on several types of cancer (such as liver cancer cells, breast cancer, colorectal, leukemia, lung cancer, and oral cancer) with varying success. This review aims to explore the current state of the latest anticancer activity research of MO plants in the last five years. We tried to explore the anticancer activities of MO extracts from reported in vivo and in vitro studies. We searched systematically from three databases (PubMed, Scopus, and Embase) and summarized the data. The keywords used were “Moringa oleifera” AND “anticancer” AND “in vivo” OR “in vitro”. The inclusion criteria were in vivo or in vitro experimental studies and exclusion criteria analyses i.e., in silico trials, study protocols, reviews, or observational studies. This review includes 16 papers on nonclinical studies of MO anticancer activity. Several active compounds have been purified and have reported their anticancer effectiveness, including glucomoringin-ITC/MIC-1, 7-octanoic acid, oleamide, 1-phenyl-2-pentanol, quercetin, gallic acid, p-coumaric acid, and 4-hydroxy 3 – methoxy cinnamic acid, quinic acid. There was no difference in the mechanism of anticancer action based on plant parts, leaves, roots, and seeds, even though using different extraction methods. The general mechanism of action shown was apoptotic, antiproliferative, and cytotoxic. The dose used differed depending on the type of cancer cells used. Some used conventional extraction methods, and others have used modern techniques to extract the purified active compounds from the fractionation process. Our review made it clear that MO could be an excellent and safe candidate for the development of novel therapies against cancer and was most commonly reported in MCF-7, HepG2, and HCT-116 cancer cells. In addition, the development of MO products as future cancer prevention is also interesting to be explored and developed optimally in clinical settings.